Exercise training programs and detraining in older women - Oliveira, Rafael (2017)
This study was supported by Parque de Ciência e Tecnologia do Alentejo (Science and Technology Park of Alentejo) – (Laboratory of Research in Sport and Health) (Alen-07-0262-FEDER-001883) funded by QRENINALENTEJO - Municipality of Esposende, municipal enterprise “Esposende 2000” and Escola Superior de Desporto de Rio Maior (Sports Science School of Rio Maior).